Deterrent effects of demerit points and license sanctions on drivers' traffic law violations using a proportional hazard model. (April 2018) - Lee, Jaeyeong; Park, Byung-Jung; Lee, Chungwon
Highlights: Accumulated demerit points extend compliance duration of traffic law infringers. Deterrent effects of license revocation are larger than those of license suspension. Suspension alone has limited effects on compliance duration of infringers. The evidence of this study strongly supports the necessity of revocation sanctions. The violation-prone group was identified as male motorcycle drivers under 30 years old. Abstract: Current traffic law enforcement places an emphasis on reducing accident risk from human factors such as drunk driving and speeding. Among the various strategies implemented, demerit points and license sanction systems have been widely used as punitive and educational measures. Limitations, however, exist in previous studies in terms of estimating the interaction effects of demerit points and license sanctions. To overcome such limitations, this work focused on identifying the interaction effects of demerit points and license sanctions on driver traffic violation behavior. The interaction deterrent effects were assessed by using a Cox's proportional hazard model to provide a more accurate and unbiased estimation. For this purpose, five years of driver conviction data was obtained from the Korea National Police Agency (KNPA). This data included personal characteristics, demerit point accumulation and license sanction status. The analysis showed that accumulated demerit points had specific deterrent effects. Additionally, license revocation showed consistent and significant deterrent effects, greater than those for suspension. Male drivers under their 30s holding a motorcycle license were identified as the most violation-prone driver group, suggesting that stricter testing for the acquisition of a motorcycle driver's license is needed.